Implementation of the Structured Habituation Method in the Al-Qur'an Memorization Process at Darul Ulum Elementary School, Cirebon City - Mohamad Alwi; Alif Nurul Mubarok (FASHLUNA, 2025)
This study concludes that the structured habituation method in the Qur'an memorization activity at the Darul Ulum Elementary School in Cirebon City has proven effective in developing students' discipline, motivation, and spiritual attachment to the Qur'an. This method is implemented through daily activities such as murojaah, ziyadah, and tasalsuli, supported by weekly memorization targets, daily monitoring with mutaba'ah books, and periodic evaluations. Despite facing challenges such as differences in students' memorization abilities, time constraints, and lack of family support, the school was able to overcome these challenges with an individual approach, grouping students based on ability, and active parental involvement. This study used a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The novelty of this study lies in the systematic mapping of habituation methods that not only emphasize cognitive aspects, but also strengthening students' character and spirituality, as well as emphasizing synergy between the school, teachers, the environment, and families. This research provides an important contribution to the development of an adaptive, holistic, and sustainable tahfidz education model at the elementary madrasah level.